Availability soil water in the initial conilon coffee development - Rodrigues, Rogério Rangel; Pizetta, Samuel Cola; dos Reis, Edvaldo Fialho; Garcia, Giovanni de Oliveira (Coffee Science - ISSN 1984-3909, 2015)
Abiotic stresses such as drought can significantly reduce the yield conilon coffee (Coffea canephora Pierre ex Froehner). The objective was to evaluate the influence of the fraction of available soil water on the initial development conilon coffee, evaluating with different water availability. The trial was carried out in the greenhouse of the Agricultural Science Center, Federal University of Espírito Santo, Alegre, ES, in a split-plot 4 x 5, and the plots with four levels of water deficit (100, 50, 30 and 10 % of available water in the soil), and the subplot with five assessment times (1, 30, 60, 90 and 120 days after onset of drought) in a completely randomized design with four replicates. The parameters evaluated were: matter of shoot dry, matter of the root system dry, plant height and leaf area. To evaluate the recovery of plants after drought, they are kept for 30 days with soil moisture close to field capacity. The best results of initial development conilon coffee were found when using the levels of 100 and 50% of available water in the soil there were no differences among them, however, differing from 30 to 10% of available water. Coffee subjected to longer periods of drought, significant losses in the initial development, undermining the recovery process after the plants deficit.